Pengaruh Good Corporate Governance dan Corporate Social Responsibility Terhadap Kinerja Keuangan Perbankan yang Terdaftar di BEI - M. Titan Terzaghi; Rudi Ikhsan (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to find the effect of Good Carporate Governance (GCG) and Carporate Social Responsibility (CSR) on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative method with a population of banking companies for the 2018-2020 period and a purposive sampling technique was chosen to determine 20 samples that meet the criteria. Furthermore, the data collection technique uses secondary data from annual reports and financial reports. Meanwhile, the data analysis techniques carried out included descriptive statistical analysis, classical assumption test, regression analysis including hypothesis testing, and coefficient of determination with the help of SPSS version 25 application. The results showed that there was a significant positive effect between the board of directors and financial performance. Meanwhile, no effect was found between Managerial ownership, Independent Commissioner, and CSR in the economic category on financial performance. Furthermore, it was found that there was a simultaneous significant effect between the three variables of GCG and CSR on financial performance with an effect of 31.10%. Finally, this research can have implications for companies in implementing GCG and CSR in the future.